Economic value of HPC experience for new STEM professionals: Insights from STEM hiring managers - Snapp-Childs, Winona; Costa, Claudia M.; Olds, Daniel; Snell, Addison; Wernert, Julie A.; Stewart, Craig A. (Frontiers in Research Metrics and Analytics, 2025)
PurposeThe purpose of this article is to investigate particular aspects of the STEM job market in the US. In particular, we ask: could the possession of high performance computing (HPC) skills enhance the chances of a person getting a job and/or increase starting salaries for people receiving an undergraduate or graduate degree and entering the technical workforce (rather than academia)? We also estimate the value to the US economy of practical experience offered to US students through training about HPC and the opportunity to use HPC systems funded by the National Science Foundation (NSF) and accessible nationally.MethodsInterviews and surveys of employers of graduates in STEM fields were used to gauge demand for STEM graduates with practical HPC experience and the salary increase that can be associated with the possession of such skills. We used data from the XSEDE project to determine how many undergraduate and graduate students it enabled to acquire practical proficiency with HPC.ResultsPeople with such skills who had completed an undergraduate or graduate degree received an initial median hiring salary of approximately 7%–15% more than those with the same degrees who did not possess such skills. XSEDE added approximately $10 million or more per year to the US economy through the practical educational opportunities it offered.DiscussionPractical hands-on experience provided by the US federal government, as well as many universities and colleges in the US, holds value for students as they enter the workforce.ConclusionPractical training in HPC during the course of undergraduate and graduate programs has the potential to produce positive individual labor market outcomes (i.e., salary boosts, signing bonuses) as well as to help address the shortage of STEM workers in the private sector of the US.